Bifunctional iron doped CuS catalysts towards highly efficient overall water electrolysis in the alkaline electrolyte. (1st May 2022) - Li, Xingqiu; Ye, Nini; Liu, Han; Li, Chongzhao; Huang, Yuanpeng; Zhu, Xuelong; Feng, Hailong; Lin, Jinghang; Huang, Li; Wu, Jingjie; Liu, Yang; Liang, Chenglu; et al.
Abstract: Efficient catalysts towards overall water electrolysis in alkaline electrolytes were highly desirable for the hydrogen production technology. The surface electronic states of copper in CuS nanocrystal catalysts were modified by iron doping through a simple wet-chemical method. The iron-doped CuS catalysts displayed drastically enhanced catalytic activities for overall water electrolysis in the strong alkaline electrolyte of 1 M KOH after a simple cyclic voltammetry activation. The optimized catalytic performance for overall water electrolysis was achieved in the CuFe0.6 S1.6 catalyst, which exhibited a low overpotential of −237 mV for HER and 302 mV for OER to reach 10 mA cm −2 . The high activities for overall water electrolysis in CuFe0.6 S1.6 were induced by the enhanced charge transfer from Cu to S via iron doping, which not only modified the surface electronic state of copper but also enhanced charge transfer during the electrochemical reactions. Moreover, the catalysts displayed satisfying stability for over 20 h at a high current density of 300 mA cm −2 for both HER and OER, showing great potential for industrial water electrolysis. Highlights: The surface electronic states of copper in CuS nanocrystal catalysts were modified by iron doping. The iron doped CuS was explored as bifunctional catalyst for overall water electrolysis to produce hydrogen. The optimized catalytic performance for overall water electrolysis was achieved in the CuFe0.6 S1.6 catalyst. The underneath mechanism for enhanced overall water electrolysis in CuFe0.6 S1.6 was discussed.